Interaction between cannabinoid type 1 and type 2 receptors in the modulation of subventricular zone and dentate Gyrus neurogenesis - Rodrigues, Rui S. (2021)
Copyright © 2017 Rodrigues, Ribeiro, Ferreira, Vaz, Sebastião and Xapelli. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY). The use, distribution or reproduction in other forums is permitted, provided the original author(s) or licensor are credited and that the original publication in this journal is cited, in accordance with accepted academic practice. No use, distribution or reproduction is permitted which does not comply with these terms.